Creativity through Connectedness: The Role of Closeness and Perspective Taking in Group Creativity. Issue 3 (3rd July 2018) - Oztop, Pinar; Katsikopoulos, Konstantinos; Gummerum, Michaela
Abstract : Achievements in various fields of creativity are resulting more and more from collaborative teams. This research investigated the role of interpersonal process variables, namely closeness and perspective taking in group creativity, with a 2 by 2 experimental design. Sixty-one 3-person groups assigned to 4 conditions (a: closeness and perspective taking, b: perspective taking, c: no closeness and no perspective taking, d: closeness). Group members collaboratively wrote stories that were rated by 3 independent expert judges. There was a positive main effect of closeness and negative main effect of perspective taking on group creativity scores. Moreover, the significant interaction between perspective taking and closeness displayed that combination of closeness with perspective taking negatively affect group creativity. These results indicate that closeness might be beneficial for group creativity only when it is not accompanied with perspective taking.